(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to describe the clinical and paraclinical characteristics of patients with gastric cancer undergoing laparoscopic distal gastrectomy with D2 lymph node dissection at Nghe An General Friendship Hospital. Methods: A cross-sectional descriptive study was conducted on 90 patients diagnosed with gastric adenocarcinoma. Data were collected from medical records, preoperative laboratory and imaging results, and endoscopic findings. Results: Most patients presented with abdominal pain (97.8%), loss of appetite (84.4%), weight loss (77.8%), and belching or acid reflux (54.4%). The mean body mass index (BMI) was 20.57 ± 2.03 kg/m², with the majority falling within the normal range (81.1%). Regarding ASA score, most patients were classified as ASA 2 (46.7%) and ASA 3 (43.3%). Most lesions were ulcerative or ulcerative-vegetative in nature. Computed tomography revealed gastric wall thickening in 85.6% of cases and staging was primarily T3 (57.8%) and T4a (20%). Conclusion: Patients with advanced-stage gastric cancer exhibited prominent clinical and paraclinical features, which are crucial for guiding appropriate laparoscopic surgical interventions.